Disseminated fungal infection complicated with pulmonary haemorrhage in a case of acute myeloid leukaemia. Issue 901 (1st November 2000) - Thulkar, S; Sharma, S; Das, P K; Kumar, L
Abstract : Pulmonary haemorrhage is a common necropsy finding in acute leukaemia, however, it is rarely diagnosed during life. A man with acute myeloid leukaemia is reported who presented with disseminated fungal infection, anaemia, thrombocytopenia, and subconjuctival and petechial haemorrhages. During the course of the patient's illness, the chest infection was complicated with bilateral pulmonary haemorrhage. The diagnosis of pulmonary haemorrhage was based on characteristic clinical and radiological findings. The patient improved on treatment.